740 Transrenal Endovascular Abdominal Aortic Aneurysm Repair in Infrarenal Abdominal Aortic Aneurysms with Anatomically Challenging Neck outside the Indications for Use: A Novel Approach. (4th May 2021) - Premnath, S; Hostalery, A; Bungay, P; Rowlands, T; Quarmby, J; Singh, S
Abstract: Introduction: Transrenal Endovascular Abdominal Aortic Aneurysm Repair (EVAR) is a novel approach for Infrarenal Abdominal Aortic Aneurysms (AAA) with unfavourable neck anatomy. This study aims to evaluate the long and short-term outcomes of Transrenal EVAR. Method: Data of patients who underwent Transrenal EVAR in a single centre over 6 years were collected. Follow up on complications and mortality for 3 years post-procedure were analysed. Results: A total of 36 patients were identified with a mean age of 77 years (61–89 years). Neck: : anatomy: : 32 (88.9%) cases had a proximal neck < 15mm. 21 (58.3%) had significant neck thrombus and 27(75%) had significant neck calcification. 11 (30.6 %) had an infra-renal neck angulation > 60 0 and 21 cases (58.3%) had an unfavourable shape. Outcome: : Post-procedure 30-day mortality was 5.6%. 4 developed renal dysfunction. The 3-year mortality was 33.3%, only 2 patients (5.6%) died of the aneurysm related complication. 7 (19.4%) patients developed endoleak. 5 patients (13.9 %) underwent reinterventions in 3 years. Conclusions: In view of the acceptable short term and long-term outcomes, trans renal EVAR can be offered for patients with infrarenal AAA with technically challenging neck anatomy but unfit for open repair in centres with adequate expertise.